The Role of Corrective Feedback in Developing Students’ Speaking Skills in EFL Conversation Classes - Anastasia Bawut; Gabriel Fredi Daar; Fidestri Riani Murdian (CV. Pusdikra Mitra Jaya, 2025)
This study aims to explore students’ perceptions of corrective feedback (CF) in EFL speaking activities and how it contributes to the development of their speaking skills. While many previous studies have focused on teachers’ perspectives and feedback strategies, this research emphasizes the students’ point of view to understand their preferences, emotional responses, and perceived benefits regarding CF. The study employed a quantitative descriptive method using a questionnaire distributed to EFL students. The data were analysed to identify patterns in students’ attitudes toward various types and timings of feedback. The findings reveal that students generally have a positive perception of corrective feedback. Most respondents agreed that CF helps them improve their speaking performance, particularly in areas such as vocabulary, pronunciation, and fluency. Contrary to common concerns among educators, the majority of students did not feel embarrassed or demotivated when corrected. Instead, they reported increased confidence and motivation when their errors were addressed constructively. Furthermore, students expressed a preference for both immediate and delayed feedback, indicating flexibility and awareness of different instructional strategies. The study suggests that corrective feedback plays a significant role in supporting learners’ speaking development. It also highlights the importance of incorporating student perspectives when designing effective feedback practices in EFL classrooms.